Damage prediction of concrete gravity dams subjected to penetration explosion. (January 2023) - Wang, Gaohui; Shu, Yizhan; Lu, Wenbo; Chen, Ming; Pan, Xinhao; Lu, Ang
Highlights: Blast tests are conducted to obtain damage mechanisms and failure modes of the dam. A CEL method is adopted to describe the dam to penetration explosion. The effects of main influential factors on the damage ranges are discussed. A damage prediction method for concrete gravity dams is put forward. Abstract: The dynamic responses and damage mechanisms of high dams that are subjected to blast loads have become important in recent years. A series of analytical, experimental, and numerical approaches are used to investigate the mechanisms and characteristics of composite damage to concrete gravity dams subjected to penetration explosion. The potential failure modes of the dam resulting from penetration explosion are first analyzed and categorized. Field blast tests are performed to gain the possible damage mechanisms and modes of a small-scale dam model to internal explosion. A fully coupled Eulerian–Lagrangian approach is then adopted and verified through comparisons between the experimental and the numerical results. Following this, detailed numerical simulations and analyses of a typical concrete gravity dam to penetration explosion are presented by using the validated numerical method to examine its dynamic responses and the development of damage in it. Furthermore, the results of damage to the dam in case of different attack locations, explosive equivalents, penetration depths, and critical interfaces are compared. Similarity theory and blasting theory are used to provide a theoretical analysis, and its results are used along with those of numerical simulations to obtain a formula to predict the damage range of the dam. The work here focuses on the dynamic responses and damage mechanisms of dams subjected to penetration explosion, and the authors propose a quantitative and effective method to predict this damage.